Engineering aspects of microbial exopolysaccharide production. (December 2017) - Freitas, Filomena; Torres, Cristiana A.V.; Reis, Maria A.M.
Graphical abstract: Highlights: Microbial EPS producers: bacteria, fungi and microalgae. EPS production by extremophiles. Mixed microbial consortia: alginate-like EPS. Cultivation mode and process operation conditions. Different bioreactor design for microbial EPS production. Abstract: Although the ability to secrete exopolysaccharides (EPS) is widespread among microorganisms, only a few bacterial (e.g. xanthan, levan, dextran) and fungal (e.g. pullulan) EPS have reached full commercialization. During the last years, other microbial EPS producers have been the subject of extensive research, including endophytes, extremophiles, microalgae and Cyanobacteria, as well as mixed microbial consortia. Those studies have demonstrated the great potential of such microbial systems to generate biopolymers with novel chemical structures and distinctive functional properties. In this work, an overview of the bioprocesses developed for EPS production by the wide diversity of reported microbial producers is presented, including their development and scale-up. Bottlenecks that currently hinder microbial EPS development are identified, along with future prospects for further advancement.